The Impact of Carbon Disclosure on Company Competitiveness: Evidence from Publicly Listed Companies - Jun Qiaofeng (IHSA Institute, 2025)
Carbon disclosure has become an increasingly important aspect of corporate sustainability as companies respond to climate change, growing Environmental, Social, and Governance (ESG) expectations, and expanding regulatory requirements for environmental transparency. Transparent carbon reporting is expected to enhance corporate competitiveness by strengthening stakeholder trust, improving corporate reputation, attracting sustainable investment, and supporting long-term strategic positioning. This study aims to examine the impact of carbon disclosure on company competitiveness. A quantitative explanatory research design was employed using a cross-sectional survey of 180 publicly listed companies that publish sustainability reports. The sample was selected through purposive sampling based on predefined eligibility criteria. Data were collected using structured questionnaires and supported by corporate sustainability reports, and subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that carbon disclosure has a positive and statistically significant effect on company competitiveness. Companies with higher levels of environmental transparency demonstrate stronger competitive performance through improved corporate reputation, greater investor confidence, enhanced stakeholder trust, and increased operational effectiveness. These findings suggest that effective carbon disclosure serves not only as a regulatory compliance mechanism but also as a strategic business tool for creating sustainable competitive advantage. Therefore, companies are encouraged to integrate carbon disclosure into their broader sustainability initiatives and business strategies to achieve long-term value creation and organizational competitiveness.